2007
DOI: 10.1111/j.1728-4457.2007.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Son Preference in South Korea: The Roles of Development and Public Policy

Abstract: For years, sex ratios at birth kept rising in South Korea despite rapid development. We show that this was not an anomaly: underlying son preference fell with development, but the effect of son preference on sex ratios at birth rose until the mid-1990s as a result of improved sex-selection technology. Now South Korea leads Asia with a declining sex ratio at birth. We explore how son preference was affected by development and by public policy. Decomposition analysis indicates that development reduced son prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(214 citation statements)
references
References 32 publications
11
203
0
Order By: Relevance
“…The trends in parity progression ratios demonstrate that the decline in fertility spread from the most-educated to the least-educated groups during the fertility transition, and that the norm of a two-child family became established across all social strata in Korea. Such a rapid transformation of fertility patterns cannot occur without the extensive diffusion and social interactions of small family norms and contraceptive use, as prior research has discussed (Chung and Das Gupta 2007;Kye 2012;Montgomery and Chung 1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The trends in parity progression ratios demonstrate that the decline in fertility spread from the most-educated to the least-educated groups during the fertility transition, and that the norm of a two-child family became established across all social strata in Korea. Such a rapid transformation of fertility patterns cannot occur without the extensive diffusion and social interactions of small family norms and contraceptive use, as prior research has discussed (Chung and Das Gupta 2007;Kye 2012;Montgomery and Chung 1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, changes in stated son preferences might reflect the start of long-standing social processes that will eventually translate into declining sex ratios in India. For example, in South Korea sex ratios initially remained skewed even as stated son preference declined; however, by the early 1990s skewed sex ratios at birth had steadily declined and stated son preferences and sex ratios converged (Chung and Das Gupta 2007). Regardless, son preference cannot be equated with sex ratios, and they should be examined as separate but related social phenomena.…”
Section: Stated Son Preference Outcomementioning
confidence: 99%
“…These types of behaviors are especially likely to occur in countries with relatively low or declining fertility, where birth control is widely available. For example, Chung and Das Gupta (2007) found that son preference is a significant factor that influences the practice of induced abortion among women in South Korea. Also, based on the results of a longitudinal study of Matlab in Bangladesh, Bairagi (2001) reported that the effect of son preference on abortion and fertility behavior became stronger with declining fertility, because couples strive to have a certain number of sons and daughters within a smaller family size.…”
Section: Introductionmentioning
confidence: 99%